2022
DOI: 10.3390/healthcare10122442
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Juggling-Based Motor Learning Physical Activity on Well-Being in Elderly: A Pre–Post Study with a Special Training Protocol

Abstract: Background: The importance of physical activity for the elderly is undeniable. Specific forms of exercise that are able to engage practitioners, both cognitively and physically, may provide more positive consequences for health and quality of life. Juggling is one of these activities that has both of these characteristics. Methods: Twenty elderly people (70.55 ± 4.91) were included in a juggling-based motor learning protocol for twelve training units during one month of exercising. An evaluation of the propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Although this form of exercise seems demanding, research confirms that older people are fit enough to master juggling exercises [11,34]. One of the positive aspects of taking up this form of exercise is the growing evidence indicating that juggling improves the well-being of exercisers [34,[36][37][38]. In addition, our previous research showed that this form of exercise is attractive to older people [34].…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…Although this form of exercise seems demanding, research confirms that older people are fit enough to master juggling exercises [11,34]. One of the positive aspects of taking up this form of exercise is the growing evidence indicating that juggling improves the well-being of exercisers [34,[36][37][38]. In addition, our previous research showed that this form of exercise is attractive to older people [34].…”
Section: Introductionmentioning
confidence: 93%
“…One such activity that can engage both cognitively and physically and will be a novelty for potential participants is juggling [33,34]. Classical juggling is a form of activity that requires simultaneous throwing and catching of balls (or other objects like, rings, clubs, scarves) individually with one or both hands in a specific sequence without dropping them [34,35].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations